Ovarian cancer derived extracellular vesicles promote the cancer progression and angiogenesis by mediating M2 macrophages polarization - Xue Tang; Chengbin Ma; Qiongwei Wu; Meng Yu (BMC, 2024)
Abstract Background Extracellular vesicles (EVs) are mediators between cancer cells and other types of cells, such as tumor-associated macrophages (TAMs), in the tumor microenvironment. EVs can remodel the tumor microenvironment and regulate tumor progression. However, the underlying molecular mechanism of these interactions remains unclear. Methods First, we explored the effect of TAMs on the survival prognosis of patients with ovarian cancer. Next, we isolated EVs derived from ovarian cancer cells (OV-EVs) through ultracentrifugation and analyzed the capacity of OV-EVs to regulate macrophage polarization in ovarian tumors and in whole peripheral blood. Moreover, we explored the roles of OV-EVs-induced macrophages in tumor progression through in vitro and in vivo assays. Results OV-EVs were encapsulated by macrophages and induced the polarization of macrophages toward the M2 phenotype. Moreover, OV-EVs-induced M2 macrophages promoted angiogenesis and cancer progression both in vitro and in vivo. In addition, OV-EVs-induced macrophages increased the expression level of VEGF and increased the expression level of VEGFR in tumors, which resulted in angiogenesis in ovarian cancer. Conclusions The present study demonstrated that OV-EVs induce M2 polarization in macrophages and promote the progression of ovarian cancer. This study provides novel insight into the mechanism of ovarian cancer progression.